Synergistic Effects of Hybrid Montmorillonite and Graphene Nanoplatelets on the Mechanical, Thermal, and Structural Properties of Epoxidized Palm Oil/Epoxy Composites - Mustapha, Rohani; Zulkefli, Nur Aliaa; Jusoh, Suriani Mat; Mustapha, Siti Noor Hidayah; Ghazali, Che Mohd Ruzaidi (Archives of Metallurgy and Materials, 2026)
Vegetable oils (VOs) are increasingly recognized as promising renewable alternatives to traditional epoxy resins. However, their relatively modest mechanical and thermal properties often hinder broader application. To overcome these limitations, this study focused on enhancing the performance of epoxy/epoxidized palm oil (EEPO) through a synergistic reinforcement strategy involving hybrid nanofillers. The hybrid filler systems were developed by combining a fixed amount of graphene nanoplatelets (GNP) at 0.5 phr with varying loadings of montmorillonite (MMT) at 1.0, 1.5, and 2.0 phr. The hybrid fillers were incorporated into the developed resin system to evaluate their synergistic effects on the overall performance of the composite. Comprehensive characterization, including X-ray diffraction (XRD), scanning electron microscopy (SEM), flexural testing, and thermal analyses such as differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), was conducted to examine the structural, mechanical, and thermal behavior of the resulting composites. The hybrid composite containing EEPO/GNP-MMT (0.5:1.0) achieved the highest performance, with a 37.7% increase in flexural strength (86.31 MPa), a 9.5% increase in flexural modulus (2.87 GPa), and a 20.6% increase in glass transition temperature (67.79°C). TGA results revealed improved thermal stability due to the enhanced barrier effects and the filler-matrix interfacial bonding. These results highlight the synergistic role of hybrid MMT and GNP fillers in producing sustainable, high-performance epoxy composites for structural applications, protective coatings, and bio-based panels.